Enabling the International Criminal Court to Punish Aggression - Benjamin B. Ferencz (Washington University Global Studies Law Review, 2007)
According to Article Five of the Rome Statute, the International Criminal Court (ICC) cannot exercise its jurisdiction over the crime of aggression until amendments are adopted: (1) defining the crime; and (2) setting out the conditions, consistent with the United Nations (U.N.) Charter, under which the ICC is to act. This Essay analyzes the problems posed by these stipulated requirements, and suggests solutions to fulfill them.
Keywords: Aggression (International law); Jurisdiction (International law); International; International Criminal Court